2019
DOI: 10.1289/ehp3655
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Cadmium Exposure and Bone-Related Biomarkers: A Longitudinal Study in Children

Abstract: Background:Chronic cadmium exposure has been associated with osteotoxicity in adults, but little is known concerning its effects on early growth, which has been shown to be impaired by cadmium.Objectives:Our objective was to assess the impact of early-life cadmium exposure on bone-related biomarkers and anthropometry at 9 y of age.Methods:For 504 children in a mother–child cohort in Bangladesh, cadmium exposure was assessed by concentrations in urine (U-Cd, long-term exposure) and erythrocytes (Ery-Cd, ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The results reported in recent years have provided evidence that even low chronic exposure to this metal is hazardous to health [14]. The effects of exposure to cadmium involve damage to numerous tissues and organs, including the kidneys [5, 6], liver [7, 8], bone system [9, 10], cardiovascular system [11, 12], and contribute to the development of neoplastic diseases [13, 14] and oral disorders [1517]. Smoking is the primary source of Cd exposure, especially in relation to oral health, mainly in people living in the areas with low level of cadmium pollution and no occupational exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The results reported in recent years have provided evidence that even low chronic exposure to this metal is hazardous to health [14]. The effects of exposure to cadmium involve damage to numerous tissues and organs, including the kidneys [5, 6], liver [7, 8], bone system [9, 10], cardiovascular system [11, 12], and contribute to the development of neoplastic diseases [13, 14] and oral disorders [1517]. Smoking is the primary source of Cd exposure, especially in relation to oral health, mainly in people living in the areas with low level of cadmium pollution and no occupational exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lead exposure, chronic cadmium exposure is also closely related to osteoporosis ( 35 ), and can even affect bone development in children. Malin et al ( 36 ) tested 504 children in a mother-infant cohort in Bangladesh using blood and urine cadmium concentration levels and biomarkers for bone remodeling at the ages of 9 and 4.5, as well as during pregnancy. It was found that cadmium exposure in children caused abnormal bone development, which was negatively correlated with abnormal bone metabolism indicators such as vitamin D3 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“… 29 33 Furthermore, the exposure to metals has also been assessed at 4.5 and 9 years of age in a smaller subsample of the MINIMat children (born at the hospital in Matlab between June 2003 and June 2004; at the 9-y follow-up) to evaluate the impact on immune function. 34 , 35 The girls and their mothers in this rural setting are primarily exposed to cadmium through their diet, 36 which is largely based on rice, known to easily take up cadmium from the soil. 18 Lead exposure occurs mainly through food and drinking water, dust, housing materials, and various utensils.…”
Section: Methodsmentioning
confidence: 99%